Genetic dissection of interaction between poliovirus 3D polymerase and viral protein 3AB. - Hope, D A (1997)
Poliovirus RNA-dependent RNA polymerase 3D and viral protein 3AB are both thought to be required for the initiation of RNA synthesis. These two proteins physically associate with each other and with viral RNA replication complexes found on virus-induced membranes in infected cells. An understanding of the interface between 3D and 3AB would provide a first step in visualizing the architecture of the multiprotein complex that is assembled during poliovirus infection to replicate and package the viral RNA genome. The identification of mutations in 3D that diminish 3D-3AB interactions without affecting other functions of 3D polymerase is needed to study the function of the 3D-3AB interaction in infected cells. We describe the use of the yeast two-hybrid system to isolate and characterize mutations in 3D polymerase that cause it to interact less efficiently with 3AB than wild-type polymerase. One mutation, a substitution of leucine for valine at position 391 (V391L), resulted in a 3AB-specific interaction defect in the two-hybrid system, causing a reduction in the interaction of 3D polymerase with 3AB but not with another viral protein or a host protein tested. In vitro, purified 3D-V391L polymerase bound to membrane-associated 3AB with reduced affinity. Poliovirus that contained the 3D-V391L mutation was temperature sensitive, displaying a pronounced conditional defect in RNA synthesis. We conclude that interaction between 3AB and 3D or 3D-containing polypeptides plays a role in RNA synthesis during poliovirus infection.